Effect Of Trust And Risk On Purchase Intention Using Gojek Application - Satriadi Satriadi; Ronaldo Yolanda Putra; Surya Kusumah; Selvi Fauzar; Hendri Herman (International Journal of Islamic Business and Management Review, 2022)
Transactions using the Gojek application are considered to be more practical. However, transacting using online applications cannot be separated from the uncertainty felt by consumers and is considered as a perceived risk that will be able to affect the trust and purchase intention of consumers to transact online. The main purpose of this study was to determine the effect of trust and perceived risk on purchase intention. This study uses primary data with a population of students of STIE Tanjungpinang Development users of the Gojek application and a sample of 215 respondents using purposive sampling. The analysis uses SPSS 25. The results show that it has a significant effect on purchase intention, perceived risk has a significant effect on purchase intention, and simultaneously purchase intention is influenced by trust and perceived risk.